Les clivages institutionnels souffrances de l’entre soi au travail - Sydney Gaultier (Perspectives Interdisciplinaires sur le Travail et la Santé)
In institutions in the social and health sectors, divisions within teams are an almost inherent part of their makeup. The interdependent nature of the teams and their work focusing on caregiving relationships produce a defensive group mode with complex ramifications and detrimental effects. Such divisions fall into a scenario of exclusion and a logic of rivalry among colleagues. The human suffering generated by this phenomenon and the negative consequences for the people receiving aid remain understudied. In this regard, the present paper offers a clinical outlook based on team meetings and sessions where practices were analysed. These different work contexts among educational, paramedical, and management teams made it possible to interpret institutional divisions as boundaries and to develop a typology of stable/organised divisions versus unstable/disorganised divisions. The paper explores these different aspects, looking at the suffering and probable evolution of these kinds of organisations. Finally, the paper suggests possible avenues for breaking down these divisions, in the form of recommendations and institutional mechanisms.